DIGITAL PARENTAL DELEGATION IN ISLAMIC EDUCATION FOR CHILDREN: MILLENNIAL MOTHERS' PRACTICES IN RURAL INDONESIA IN UTILIZING ELECTRONIC MEDIA - Ruswan Ruswan; Raharjo Raharjo; Ismail Ismail (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to analyze the practice of digital parental delegation in Islamic education for children carried out by parents of millennial generation. The research uses a qualitative approach with phenomenological design to understand the experiences and meanings constructed by parents in digital-based religious parenting practices. Data were collected through unstructured in-depth interviews and participatory observations, then analyzed using an interactive analysis model developed by Matthew B. Miles and A. Michael Huberman. The results of the study showed that the practice of digital parental delegation in Islamic education carried out by millennial parents’ in Sangubanyu Village, Batang Regency, reflects the transformation of religious parenting patterns in contemporary Muslim families. Parents’ no longer fully position themselves as the main source of religious knowledge, but use digital media as pedagogical partners in the process of children's religious learning. This delegation emerged as an adaptive response to time constraints, the demands of domestic and public roles, and the doubts of some parents’ about their own religious literacy. In the perspective of Social Learning Theory, digital devices serve as new religious socialization agents that strengthen memory, encourage imitation of religious behavior, and increase motivation for independent learning. Nevertheless, the findings of the study also showed a subtle shift in the authority of religious education in the family, where the role of parents is beginning to share space with algorithms, content creators, and digital platforms.